Mineral analysis of phosphate rock as Iraqi raw fertilizer - Owaid, Mustafa N; Abed, Idham A (International Journal of Environment, 2015)
This paper was assessed the mineral elements level (Co, Pb, Cr, Fe, Ni, Cu, Zn, Cd and Mn) in raw phosphate rock (PRock) that obtained from State Company For Phosphate in Anbar province. This work was achieved to add new data of microelements toward this raw local fertilizer. PRock become important as natural fertilizer to plant and mushroom due to many trace minerals. DOI: http://dx.doi.org/10.3126/ije.v4i2.12667 International Journal of Environment Vol.4(2) 2015: 413-415